Body Condition Score (BCS) Sapi Pesisir Di Kecamatan Lengayang, Kabupaten Pesisir Selatan, Sumatera Barat - Adisti Rastosari; Tinda Afriani; James Hellyward; Syahrial Syahrial (Wahana Peternakan, 2022)
Abstract This study aimed to determine the Body Condition Score (BCS) in Pesisir cattle. The Pesisir cattle used were 200 heads, which were located in Lengayang District, Pesisir Selatan Regency, Sumatera Barat Province. Research data was collected using a survey method by direct observations in the field and interviews with farmers. The research variable that was observed was the Body Condition Score (BCS). BCS value was measured using a scale of 1-3 (thin/medium/fat). The proportion of Pesisir cattle with BCS 1, 2, 3 was 14.5%, 70.5% and 15.0%, respectively. The BCS value of Pesisir cattle owned by farmers in the research location was in the normal range which refers to the standard BCS value of 1-3.  Keyword: Body Condition Score, Pesisir cattle